Insula and inferior frontal triangularis activations distinguish between conditioned brain responses using emotional sounds for basic BCI communication - van der Heiden, Linda; Liberati, Giulia; Sitaram, Ranganatha; Kim, Sunjung; Jaśkowski, Piotr; Raffone, Antonino; Olivetti Belardinelli, Marta; Birbaumer, Niels; Veit, Ralf (Frontiers in Behavioral Neuroscience, 2014)
In order to enable communication through a brain-computer interface (BCI), it is necessary to discriminate between distinct brain responses. As a first step, we probed the possibility to discriminate between affirmative (“yes”) and negative (“no”) responses using a semantic classical conditioning paradigm, within an fMRI setting. Subjects were presented with congruent and incongruent word-pairs as conditioned stimuli (CS), respectively eliciting affirmative and negative responses. Incongruent word-pairs were associated to an unpleasant unconditioned stimulus (scream, US1) and congruent word-pairs were associated to a pleasant unconditioned stimulus (baby-laughter, US2), in order to elicit emotional conditioned responses (CR). The aim was to discriminate between affirmative and negative responses, enabled by their association with the positive and negative affective stimuli. In the late acquisition phase, when the US were not present anymore, there was a strong significant differential activation for incongruent and congruent word-pairs in a cluster comprising the left insula and the inferior frontal triangularis. This association was not found in the habituation phase. These results suggest that the difference in affirmative and negative brain responses was established as an effect of conditioning, allowing to further investigate the possibility of using this paradigm for a binary choice BCI.